2017
DOI: 10.1109/tdmr.2017.2737829
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Stable Sintered Silver Die Attach for Demanding High-Power/Temperature Applications

Abstract: Abstract:A novel and simple processing step has been demonstrated to produce thermally stable sintered silver nanoparticles structures. Sintered silver has been investigated as a die attach to resolve the long-standing demand for a reliable material to enable high power/temperature electronics operating above 300 °C. However, it is now a well-known fact that such materials undergo massive microstructural evolution at 250 °C and above, creating doubts about their longterm reliability. Here an additional process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It has been previously shown that sintered silver can be stabilised through exposure to steam, and it has also been revealed that placing the sintered silver in water before exposure to high temperatures provides the same effect [10] [11]. In the previous studies the treated samples have demonstrated stability up to at least 600 h at 300 °C, and up to at least 24 h at 350 °C and 400 °C.…”
Section: A) Sintered Silver Stabilisationmentioning
confidence: 96%
See 3 more Smart Citations
“…It has been previously shown that sintered silver can be stabilised through exposure to steam, and it has also been revealed that placing the sintered silver in water before exposure to high temperatures provides the same effect [10] [11]. In the previous studies the treated samples have demonstrated stability up to at least 600 h at 300 °C, and up to at least 24 h at 350 °C and 400 °C.…”
Section: A) Sintered Silver Stabilisationmentioning
confidence: 96%
“…Silver nanoparticle paste from NBE Tech, LLC, NanoTach® X-Paste was chosen for this work due to the numerous previous studies of this and similar systems [10]. The material is recommended for die sizes of up to 10×10 mm with a pressure-less sintering process, and peak sintering temperature of 255 Cº for 25 minutes.…”
Section: A) Sintered Silver Stabilisationmentioning
confidence: 99%
See 2 more Smart Citations